2015
DOI: 10.1111/febs.13207
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptors α and β have different roles in the induction and trafficking of progesterone receptors in hypothalamic ventromedial neurons

Abstract: Progesterone receptor (PR) activation in the ventrolateral division of the hypothalamic ventromedial nucleus (VMNvl) is essential for promoting female sexual behavior. Estrogen receptor (ER) a, in contrast to ERb, has been implicated in the induction of PRs. The simultaneous activation of ERa and ERb, although not increasing the number of PR-immunoreactive neurons in the VMNvl, facilitates lordosis, which suggests that ERb and/or the ERa-ERb interaction might play a role in PR dynamics and/or PR expression by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 59 publications
1
7
0
Order By: Relevance
“…Our findings corroborate the results of previous studies showing that the activation of ERα but not that of ERβ results in increased uterine weight 24, 25 . Uncontrolled uterine epithelial cell proliferation may lead to a pathological condition such as endometrial hyperplasia, which is a premalignant lesion of endometrial cancer 28 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings corroborate the results of previous studies showing that the activation of ERα but not that of ERβ results in increased uterine weight 24, 25 . Uncontrolled uterine epithelial cell proliferation may lead to a pathological condition such as endometrial hyperplasia, which is a premalignant lesion of endometrial cancer 28 .…”
Section: Discussionsupporting
confidence: 92%
“…However, recent data suggest a possible tumour-suppressive role of ERβ 1923 . Moreover, some studies indicate that activation of ERβ alone does not result in increased uterine weight 24, 25 . Therefore, selective activation of ERβ may be a safer approach to HRT than the common use of oestrogen, with respect to the risk of developing endometrial hyperplasia and cancer 26 .…”
Section: Introductionmentioning
confidence: 99%
“…Although estradiol priming through ERα is sufficient for upregulation of PGR and facilitation of lordosis [62], there is evidence that ERα and ERβ both have a role PGR induction [80]. However, simultaneous ERα and ERβ activation does not replicate estradiol treatment, pointing to the involvement of an additional ER, such as GPER, which induces enough PRG for progesterone for a moderate level lordosis [81].…”
Section: Membrane Estrogen Receptors Regulating Sexual Receptivitymentioning
confidence: 99%
“…The differential local distribution of ERs most likely indicates the different effects of local E2 administration in the brain [60]. Evidence has revealed that the individual or simultaneous activation of ERα and ERβ has different effects [61]. These findings suggest the intriguing hypothesis that the interactions between the two ERs and the consequences of transcriptional modulation are complicated and delicately balanced.…”
Section: The Genomic Actions Of Estrogens In Synaptic Plasticitymentioning
confidence: 99%